INFANCY MALTREATMENT PREVENTION: A PROGRAM IMPACT ON CHILD DEVELOPMENT - Cerezo, M. Angeles; Dolz, Laura; Pons-Salvador, Gemma; Cantero, M. José (Anales de Psicología / Annals of Psychology, 1999)
The program "Mother-child Psychological Support" is a preventive action focused on babies from 0 to 18 month old, because these children are a particularly vulnerable group to parental practices at risk of child maltreatment. The primary goal is aimed at supporting and promoting parental competency in the parent- child relationship context. The purpose of this study, that is part of larger investigation, was to test the impact of the program on child development. Positive gains in child development were considered as indirect index of greater mothers’ involvement in their children’ developmental processes. Two-hundred forty children, from 0-18 month old, were the participants in this study (six experimental and six control groups). As it was expected, program children showed significantly higher overall DQs, from the fourth visit and on, than their counterparts. Findings regarding specific areas, such as adaptive behavior and fine motor behavior showed similar trends. Gross motor behavior showed no particular impact of the program. Implications of these findings were discussed.